2013
DOI: 10.1021/om301079u
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigations and Secondary Coordination Sphere Effects in the Hydration of Nitriles with [Ru(η6-arene)Cl2PR3] Complexes

Abstract: The mechanism of the nitrile-to-amide hydration reaction using [Ru(η 6 -arene)Cl 2 (PR 3 )] complexes as catalysts was investigated (η 6 -arene = C 6 H 6 , p-cymene, C 6 Me 6 ; R = NMe 2 , OMe, OEt, Et, iPr). Experiments showed that the mechanism involves the following general sequence of reactions: substitution of a chloride ligand by the nitrile substrate, intermolecular nucleophilic attack by water to form an amidate intermediate, and dissociation of the resulting amide. The effects of secondary coordinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 49 publications
1
60
0
1
Order By: Relevance
“…The poor reactivity observed was ascribed to the low stability of the cyanohydrin substrates, which slowly equilibrate in solution with HCN and the corresponding aldehyde or ketone (Scheme 23), and the irreversible coordination of the cyanide anion to platinum leads to the deactivation of the catalyst. In fact, most of the nitrile hydration catalysts reported to date are poisoned by cyanide and, therefore, with some notable exceptions [84][85][86][87][88][89], are inoperative with this particular class of nitriles. Although with only one example, Parkins and co-workers showed that this limitation can be circumvented, protecting the OH group of the cyanohydrin prior to the hydration reaction [90].…”
Section: Limitationsmentioning
confidence: 99%
“…The poor reactivity observed was ascribed to the low stability of the cyanohydrin substrates, which slowly equilibrate in solution with HCN and the corresponding aldehyde or ketone (Scheme 23), and the irreversible coordination of the cyanide anion to platinum leads to the deactivation of the catalyst. In fact, most of the nitrile hydration catalysts reported to date are poisoned by cyanide and, therefore, with some notable exceptions [84][85][86][87][88][89], are inoperative with this particular class of nitriles. Although with only one example, Parkins and co-workers showed that this limitation can be circumvented, protecting the OH group of the cyanohydrin prior to the hydration reaction [90].…”
Section: Limitationsmentioning
confidence: 99%
“…[15,21] In the case of acetonitrile hydration catalyzedb y[ ( h 6 -p-cymene)RuCl 2 (P(NMe 2 ) 3 )],t he reaction rate increased when 1equivalent of CN À was added and decreasedw ith increasing [CN À ]. [21] The effect of cyanideo nt he catalytic activity of RuCl 2 (PTA) 4 and the in situ generated catalyst (RuCl 3 + 6PTA)w as examined. [21] The effect of cyanideo nt he catalytic activity of RuCl 2 (PTA) 4 and the in situ generated catalyst (RuCl 3 + 6PTA)w as examined.…”
Section: Temperature Studiesmentioning
confidence: 99%
“…With water as a reagent, and many of the product amides having modest water solubility,n itrile hydration is well suited towardsa queous-phase catalysis. [9,[13][14][15][16][17][18][19][20][21][22] Our group has been interested in the development of water-soluble phosphine ligandsf or use in catalysis. [1,[12][13][14][15][16][17] Ru II and Ru IV complexes with nitrogen-containing phosphine ligands (for example, [RuCl 2 (h 6 -arene)(P(NMe 2 ) 3 )]) have shown significant activity for nitrile hydration.…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic utility of complexes [RuCl 2 ( 6 -arene){P(NMe 2 ) 3 }] was further demonstrated in the challenging hydration of cyanohydrins (-hydroxynitriles), substrates usually difficult to hydrate because they degrade to produce cyanide which poisons the catalysts. As shown in Scheme 7, using 5 mol% of the pcymene complex [RuCl 2 ( 6 -p-cymene){P(NMe 2 ) 3 }] (11), and performing the catalytic reactions at room temperature within the pH range 3.5-8.5 to minimize the decomposition of the substrates into the corresponding aldehydes and HCN, glycolonitrile and lactonitrile could be completely transformed into the corresponding -hydroxyamides [48,49]. The H-bond accepting properties of tris(dimethylamino)phosphine were again evoked to explain the excellent catalytic activities observed, a cooperative effect that was supported by DFT calculations (Figure 4) [49].…”
Section: Scheme 5 Catalytic Hydration Of Nitriles Using Cis-[ru(acacmentioning
confidence: 99%
“…As shown in Scheme 7, using 5 mol% of the pcymene complex [RuCl 2 ( 6 -p-cymene){P(NMe 2 ) 3 }] (11), and performing the catalytic reactions at room temperature within the pH range 3.5-8.5 to minimize the decomposition of the substrates into the corresponding aldehydes and HCN, glycolonitrile and lactonitrile could be completely transformed into the corresponding -hydroxyamides [48,49]. The H-bond accepting properties of tris(dimethylamino)phosphine were again evoked to explain the excellent catalytic activities observed, a cooperative effect that was supported by DFT calculations (Figure 4) [49]. Secondary coordination sphere activation of water, via hydrogen bonding with the OH group of the ligand, also explains the outstanding performances of the related phosphiniteruthenium(II) complex [RuCl 2 ( 6 -p-cymene){PMe 2 (OH)}] (12), which was also able to hydrate cyanohydrins [50,51].…”
Section: Scheme 5 Catalytic Hydration Of Nitriles Using Cis-[ru(acacmentioning
confidence: 99%